EVALUATING THE IMPACT OF INTEGRATED MANAGEMENT SYSTEMS ON OPERATIONAL RISKS AND FINANCIAL PERFORMANCE IN A RESEARCH ORGANIZATION - Jonović, Marija; Jonović, Marija; Barjaktarović, Lidija; Stefanović, Nikola (The European Journal of Applied Economics, 2025)
The study builds on the findings of Jonović et al. (2024) and aims to: 1) determine whether the implementation of Integrated Management Systems (IMS) based on the Committee of Sponsoring Organizations (COSO) Enterprise Risk Management (ERM) model improves sustainable operational risk management and financial performance in a Scientific research organization; and 2) develop a method for improving operational risk management and financial outcomes. Primary research includes SWOT (Strengths, Weaknesses, Opportunities, and Threats) analyses conducted from 2021 to 2024, with an average response rate of over 71%, confirming a sustainable business context. Following the PDCA (Plan-Do-Check-Act) cycle, it strives to enhance the response of the scientific research organizations to strategic goals and operational risks. It is supported with the analysis of financial indicators, as result of the secondary research (for the same period), and Pearson’s correlation, showing the impact of IMS based on the COSO ERM model on the organization's financial and operational stability. It emphasizes the importance of effective operational risk management for better financial performance. However, it suggests that implementing IMS is not enough to improve operational risk management within the organization. Future research should investigate comprehensive methods, diverse strategies, and comparative studies to enhance operational and financial outcomes.
Keywords: Operational risks, COSO, ERM, (IMS), SWOT Analysis, Scientific research organization